Renewable energy development as a solution to rural electrification in Nigeria - Yamusa, Shehu Usman; Ansari, Abdul Haseeb (American Research Institute for Policy Development, 2015)
The ratio of electricity generated through renewable energy sources in developing and least developed countries, barring a few, are not at all significant, as due to lack of sophisticated technology and scarce financial resources. The problem of electricity in most of the African countries, despite having abundance of potential of wind and intensity of the sun is more than most part of the developing world. Most of the developing countries, including African countries get renewable energy between 1 to 3 percent. They squarely depend on gas and coal, with or without certain alternative energy sources, for power generation. Nigeria is no exception to this. In this paper, the condition of rural electrification in Nigeria is analysed with the intention to provide viable solutions for the development and provision of energy in order to reduce electricity problem among the local communities, to encourage industries with the help of the government to have some power generated from renewable energy sources, especially through PV panels, so that the burden on the central power generation sources could be reduce. The efficient electricity for the small scale industries via this source will alleviate the massive unemployment rate in the country. In view of these, the paper also examines the Nigerian power generation mix and use the idea of energy diversification method resorting to renewable energy sources readily available in the country in providing electricity in the Nigerian rural areas.